Evaluation of Papillomacular Nerve Fiber Bundle Thickness in Glaucoma Patients with Visual Acuity Disturbance. (2nd July 2020) - Takahashi, N; Omodaka, K; Pak, K; Kikawa, T; Kobayashi, W; Akiba, M; Nakazawa, T
ABSTRACT: Purpose: Assessing the papillomacular nerve fiber bundle (PMB) can identify glaucoma patients with decreased visual acuity. In this study, we explore efficient methods for evaluating PMB thickness in glaucoma patients, based on swept source-optical coherence tomography (SS-OCT). Methods: This study included 347 eyes of 205 open-angle glaucoma (OAG) patients. Patients were excluded if they had best-corrected decimal visual acuity < 0.3, axial length >28 mm, non-glaucoma ocular disease, or systemic disease affecting the visual field. We obtained vertical 12.0 × 9.0 mm 3D volume scans covering both the macular and optic disc regions with SS-OCT (DRI OCT Triton, Topcon), and measured the thickness of the PMB, as well as average macular retinal nerve fiber layer thickness (mRNFLT) and macular ganglion cell complex thickness (mGCCT) in the macular map and temporal-quadrant circumpapillary RNFL thickness (tcpRNFLT). We also measured central-strip RNFLT (csRNFLT) and GCC (csGCCT) in a 1.5 × 6.6 mm area of the scan centered between the fovea and optic nerve head. CsRNFLT and csGCCT were divided lengthwise into three 1.5 × 2.2 mm sections. We then calculated Spearman's rank correlation coefficient between these OCT measurements and visual acuity. Logistic regression analysis was used to find the cutoff value for the OCT measurements to predict logMAR < 0. Results: The correlation coefficients with logMAR were 0.38 for mRNFLT, 0.44 for mGCCT, 0.37 for middle csRNFLT, 0.50 for middle csGCCT, and 0.33 for tcpRNFLT (all P < .0001). For middle csGCCT, the area under the curve indicating decreased visual acuity was 0.80, with a cutoff value of 88.6 μm ( P < .001). Conclusions: We found strong associations between OCT parameters in the PMB, especially middle csGCCT, and visual acuity in patients with OAG. The thickness of the PMB may therefore be valuable information for glaucoma care and may help prevent visual acuity disturbance.